Green Innovation for SMEs in Indonesia – A Literature Analysis - Panuju, Achmad Yahya Teguh; Bakri, Samsul (Journal of Engineering and Scientific Research, 2024)
Improving the performance of small and medium enterprises (SME) means enhancing the economics of a nation, considering that SMEs are the biggest part in global economic activities. The higher the SME’s activities, the higher the economic growth occurs in a country. However, nurturing SMEs activities affect the environment, while the damage inclines every day in a worrying level. There is a huge demand to suppress down the environmental damage rate globally, as if it causes a contradictive goal with the economic perspective. Thus, a compromise should be made between both expectations, even it is not easy to do so. Answering to the problem, discussions have been made among scholars around the world, including in Indonesia as an emerging country. Theories and methods were proposed, varying based on characteristics in each region. Especially in Indonesia, there is a lack of literature review on this field, which is actually required to depict the current condition, to evaluate the discussion effectiveness and to develop future improvements. Therefore, this article aims to fill this gap by presenting scientific articles related to the topic and reviewing the discussion. Subsequently, a classification of the articles based on identified themes is conducted. And further the classification is used to see more specific gaps in the discussion and to provide recommendation for the next studies.